Peningkatan Kreativitas Anak dengan Implementasi Augmented Reality Pembelajaran Hewan Berbasis Android - Kusmawan, Dicky; Aryani, Diah; Yusuf, Mohamad (Universitas Mercu Buana, 2025)
This study aims to address challenges in early childhood education, which are often caused by regulations, limited educator readiness, and inadequate interactive learning media. Augmented Reality (AR) technology offers a solution by integrating the virtual and real worlds, enabling children to experience 3D objects immersively using smartphones. The research was conducted at SD Bedahan 01 with third-grade students learning Natural Science (IPA) topics about animals, including their characteristics, classifications, habitats, and benefits. Initial observations showed the average student score was 78, meeting the Minimum Competency Criteria (KKM) but requiring improvement to optimize learning outcomes. To address this, an AR-based learning media application for Android was developed using the Multimedia Development Life Cycle (MDLC) method, integrating 3D visuals, audio, and interactive features to create an engaging and immersive learning experience. The results demonstrated that the use of AR technology increased students’ interest and understanding of the material, as well as their ability to recall and apply concepts. This study highlights the potential of AR as an effective educational tool and contributes to the development of innovative and interactive learning media for elementary education, particularly in subjects requiring visualization. Future research may explore expanding AR features to include gamification and advanced interactivity for broader educational applications.